PENGARUH KOMBINASI PETRAGENOL DAN EKSTRAK JERUK TERHADAP FEEDING STRATEGY LALAT BUAH Bactrocera dorsalis - Sumarmi, Ramadhan (IAIN Batusangkar, 2011)
Petragenol is an attractant contained methyl-eugenol. It is an insect?s pheromone signaling for mating, made colony, and feeding. The oranges had too an attractants especially for fruit flies. The aim of this research was to know the influence of combination of oranges extract and petragenol to Feeding Strategy of Bactrocera dorsalis flies. This research used the Y tube method. The 60 fruit flies were used as samples. The 10 flies were placed in start chamber Y tube and in two other tips were placed the bait as a single or combinations of non-matured oranges extract and petragenol (A), matured oranges extract and petragenol (B), decay-oranges extract and petragenol (C), and petragenol as control (D). Feeding Strategy defined by the need of time to reach the bait and the spend of time in the bait with categories as activity of Searching, Grounding, Gathering, and Learning. The data analyzed by Chi-square (X2). The results showed that the fastest searching activity in B, the longest time to gathering activity in A, the longest time to grounding activity in non-matured oranges extract, and the longest time to learning activity in matured oranges extract. It can conlude that the best attractant to teas Bactrocera dorsalis Feeding Strategy are matured oranges extract-petragenol combination for Searching and Learning activity, and combination of non-matured oranges extract and petragenol to grounding and gathering activity.Key words: petragenol, oranges extract, feeding strategy